Service distribution and service discovery through a public web services platform - Wu, Chen (Curtin University, 2008)
Service-Oriented Architecture (SOA) represents an emerging architectural approach that is able to tackle challenges in the contemporary service-based economy, in which the global market revenues are shifting from the manufacture of traditional off-the-shelf products to the provision of diversified services that suffice for customers’ needs. In such a service-based economy, one can envisage an entirely “service-oriented” world, where a massive number of distributed services with different natures and capabilities are provided by various professionals around the world. Problems arise when business applications demand desirable services through different sources and providers that are appropriate for their own benefits and preferences. Therefore, it can be very challenging to design an SOA infrastructure that enables users to exploit this great level of service heterogeneity and quantity. One of the key issues in service-oriented architecture is to achieve efficient service discovery and loosely-coupled service distribution while maintaining a satisfactory degree of scalability, usability, and Web consistency. This thesis deals with SOA infrastructure-level design and implementation issues. It approaches this SOA infrastructure within the scope of Web services, which capture an important, and perhaps the best, ‘realisation’ of SOA. It investigates and formulates how public Web services distributed across the World Wide Web can be augmented by a software platform that enables scalable, user-centred,semantic-enabled, and integration-oriented service retrieval, selection, and matching. The primary goal of this thesis is thus to propose a conceptual framework of an enhanced SOA infrastructure with regard to service distribution and discovery.It also aims to design and implement a platform (PWSP), by means of which a large number of public Web services on the Web can be distributed based on service demands, retrieved based on service descriptions, selected based on service qualities, and matched based on service messages in a user-centred, scalable, and Web-consistent manner without augmenting existing Web services standards.